2011
DOI: 10.4097/kjae.2011.60.4.244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the ease of laryngeal mask airway ProSeal insertion and the fiberoptic scoring according to the head position and the presence of a difficult airway

Abstract: BackgroundThe sniffing position is recommended for conventional laryngeal mask airway (LMA) insertion. However, there has been a high success rate of LMA insertion with the head in the neutral position. The effect of a difficult airway on the ease of LMA insertion is not clear. In this study, we compared the ease of LMA ProSeal™ (PLMA) insertion and the fiberoptic scoring according to the head position and the presence of a difficult airway.MethodsAfter obtaining informed consent from the subjects, we enrolled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…There was no difference among the groups in terms of imaging classification. Jun et al [ 12 ] recorded the head position of patients and reported that the fiberoptic image does not change.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference among the groups in terms of imaging classification. Jun et al [ 12 ] recorded the head position of patients and reported that the fiberoptic image does not change.…”
Section: Discussionmentioning
confidence: 99%
“…15 Unfortunately, there are no universally recognized or adopted predictors of the difficulty of insertion of advanced supraglottic airways that are important airway adjuncts as part of the airway rescue algorithm. 16,17 There appears to be no correlation between the success of laryngeal mask placement and the Mallampati scoring system. 18 Some physical findings that may predict a difficult airway are listed in Table 6.…”
mentioning
confidence: 99%
“…A success of laryngeal mask airway insertion was defined as normal chest movement and a square wave of capnograph 20‐22 . If the third attempt failed, it was regarded as a failure.…”
Section: Resultsmentioning
confidence: 99%
“…The LMA Supreme was pressed against the hard palate and advanced into the hypopharynx until resistance was felt. The success of LMA Supreme insertion was defined as normal chest movement and a square wave of capnograph 20‐22 . Only one attempt was allowed before insertion was considered a first attempt success.…”
Section: Methodsmentioning
confidence: 99%